Effect of Vermicompost and Fertilizer Levels on Soil Properties, Yield, and Quality of Sugarcane in Calcareous Soil of Bihar - Thakur, S. K.; Jha, C. K.; Mishra, V. K. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted over three consecutive years (2015–2017) at RPCAU, Bihar, to evaluate the effects of levels of vermicompost (0, 2.5, 5.0, and 7.5 t ha-1) and 0, 50, 75, and 100% of the recommended dose of fertilizer (RDF) on soil properties, yield and quality of mid-late sugarcane variety BO 154 sugarcane grown in calcareous soils. Results showed that increasing doses of both vermicompost and fertilizers significantly enhanced the number of tillers, millable canes, and overall cane yield. The highest number of millable canes and maximum cane yield were recorded with the highest fertilizer level (100% RDF), while the maximum cane yield was observed at the highest vermicompost application rate of 7.5 t ha-1. Additionally, the interaction between vermicompost and fertilizer levels significantly influenced cane yield. Juice quality parameters such as brix, sucrose content, and purity % were not significantly impacted by the treatments. However, sugar yield followed the trends observed for cane yield. Post-harvest soil analysis revealed a significant improvement in organic carbon % and availability of nitrogen (N), phosphorus (P), and potassium (K) with increasing levels of vermicompost and fertilizers. The greatest improvements in organic carbon and nutrient availability were noted at the highest vermicompost and fertilizer doses. The application of 5.0 t ha-1 vermicompost combined with 100% RDF proved to be the most effective treatment for enhancing both cane and sugar yields in the calcareous soils of Bihar.